Gendered effects of trade restrictions on labour market outcomes in Malawi - Kankwamba, Henry (International Labour Organization, 2023)
This chapter explores the impact of tariff increases on female unemployment and the agricultural sector in Malawi. Combining a standard general equilibrium model with a top-down behavioural microsimulation, the author finds that a move towards trade restrictions would destroy over 1 million jobs in the country, affecting primarily women across the labour market but more markedly in agriculture.